2022
DOI: 10.6026/97320630018588
|View full text |Cite
|
Sign up to set email alerts
|

Impact of covid-19 on education, psychological wellness and life style of dental students in Saudi Arabia

Abstract: The COVID-19 epidemic has had a significant impact on dental education, psychological health, and students' way of life worldwide. The new methods of teaching and learning had to be adapted by dental educational institutions. Due to lifestyle changes, COVID-19 had a major negative influence on students' mental health. Therefore, it is of interest to assess depression; anxiety and stress scale (DASS-21) levels experienced by dental students and compare them with gender and course of students. A cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
0
0
0
Order By: Relevance
“…This reflects the challenges in replicating hands-on clinical training through online platforms. Notably, our findings regarding dissatisfaction rates are higher than those reported in previous studies conducted in Saudi Arabia and Oman, such as those by Al Rawahi et al and Bahanan et al [8,9], but align closely with the results reported by Abdul et al [10]. This discrepancy could be attributed to differences in the timing of data collection.…”
Section: Discussionsupporting
confidence: 86%
“…This reflects the challenges in replicating hands-on clinical training through online platforms. Notably, our findings regarding dissatisfaction rates are higher than those reported in previous studies conducted in Saudi Arabia and Oman, such as those by Al Rawahi et al and Bahanan et al [8,9], but align closely with the results reported by Abdul et al [10]. This discrepancy could be attributed to differences in the timing of data collection.…”
Section: Discussionsupporting
confidence: 86%
“…Scores for each subscale were divided into five levels: normal, mild, moderate, severe, and extremely severe. Stress was classified as normal (0-14), mild (15-18), moderate (19)(20)(21)(22)(23)(24)(25), severe (26)(27)(28)(29)(30)(31)(32)(33), and extremely severe (34+). Depression was classified as normal (0-9), mild (10-13), moderate (14-20), severe (21)(22)(23)(24)(25)(26)(27), and extremely severe (28+).…”
Section: Variablesmentioning
confidence: 99%
“…To the best of our knowledge, most of the published studies that assessed the psychological impact of COVID-19 among university students in Saudi Arabia were conducted among medical science students (26,(29)(30)(31)(32)(33)(34)(35). For example, a study was conducted to assess the prevalence of Depression, Anxiety, and Stress symptoms among medical students of Sulaiman Al Rajhi University, Al Bukayriyah, Saudi Arabia during quarantine and while learning online shortly after the announcement of documented COVID-19 cases in the Kingdom of Saudi Arabia (33).…”
Section: Introductionmentioning
confidence: 99%